Nonlinear analysis of local field potentials and motor cortex EEG in spinocerebellar ataxia 3. (January 2019) - Yu, Yi; He, Xinqi; Zhao, Zongya; Jiang, Wenshuai; Pan, Deng; Shi, Lijuan; Xu, Liuyang; Shi, Liangliang; Gu, Renjun; Wei, Jianshe
Highlights: Accurate SCA3 model identification results ensure the rationality of the experimental results. Field potential distribution parameters and EEG to explore a new basis for clinical diagnosis. It was analyzed by means of the Morris water maze test (MWM) and conform to the results of EEG signals. Abstract: This study explores the potential usefulness of EEG for patient diagnosis by analyzing SCA3 and wt mice. Self-made implantable electrodes were constructed and implanted to extract EEG signals from the cerebral motor cortex and the cerebellar areas that are affected by the disease. Nonlinear dynamic analysis and EEG energy were used to distinguish between SCA3 and WT mice, and we found that all four were increased in SCA3 mice. The alpha and theta bands of LZ complexity were significantly higher in SCA3 mice than in the control group. Therefore, it was possible to distinguish between the two groups by the LZ complexity of their alpha and theta bands. Analysis of C0 complexity and approximate entropy showed that the random part in the disease group was larger than in the control group, and that in addition the randomness was increased in SCA3 mice. The spatial learning and memory were analyzed by means of the Morris water maze test (MWM), The results showed that the swimming velocity, distance traveled and latency to reach the platform in SCA3 mice were increased when compared with WT mice during the 4 training days (p < 0.05, 0.01 or 0.001). And the results are conform to the results of EEG signals. In conclusion, EEG signals could be used to identify SCA3 in mice. They may also be clinically useful for the diagnosis of cerebellar ataxia in patients, and for additional studies aimed at gaining a deeper understanding of spinal cerebral ataxia.